A benzimidazole-based ratiometric fluorescent probe for the accurate and rapid monitoring of lysosomal pH in cell autophagy and anticounterfeiting. Issue 19 (20th September 2022) - Wen, Chaochao; Ge, Jinyin; Huang, Yu; Gong, Tao; Wang, Congying; Yu, Baofeng; Liang, Wenting
Abstract : The lysosomal targeted ratiometric fluorescent BD probe reveals excellent application performance in the fields of selective monitoring of the lysosome pH of living cells, real-time dynamic monitoring of autophagy, and document anti-counterfeiting. Abstract : The change in lysosomal pH is an important physiological indicator in the process of cell autophagy. Herein, a ratiometric fluorescent probe, 4-(2-(1 H -benzo[ d ]imidazol-2-yl)vinyl)- N, N -dimethylaniline (BD ), has been synthesized and applied for lysosomal pH detection and cell autophagy imaging. In this probe, the imidazole group and dimethylamino group possess excellent lysosomal targeting ability and the benzimidazole moiety acts as a proton reaction site. BD reveals an obvious ratiometric fluorescence emission with an ideal p K a value of 4.73 and a linear response in the range of 4.06–5.20, which is considered useful for the quantitative detection and imaging of lysosomal pH change. Meanwhile, BD exhibits a larger Stokes shift, good selectivity, strong photostability, good reversibility and good biocompatibility, which makes BD capable of being applied to complex biological environments. Ratiometric fluorescence imaging studies show that BD can selectively monitor the pH in the lysosomes of live cells, and even real-time dynamic monitoring of cell autophagy can be conducted. Moreover, BD also shows excellent application potential in the field of anticounterfeiting.